Investigating the impact of consumer trust on loyalty and purchase intention of food store brands: Case study: Palladium shopping mall in Tehran - Hosseini, Mahsa; Norouzi, Hosseini (International Review of Management and Marketing, 2017)
Today, store brand is considered as one of the active businesses in large cities and is under a lot of pressure caused by competition. The stores managers need special attention of managers in order to create and maintain competitive advantage and position in the market. The stores in order to keep pace with the values and demands of our customers and update a marketing policies, require the use of strategies that in the long run be able to create competitive advantage for own self, and achieve a lasting relationship in their relationships with customers, as the most important asset of the company. The aim of the present study is to examine the role of consumer trust in loyalty and purchase intention. By investigating this issue food sellers can develop strategies that cause long-term success for the organization. The data for this study is collected through conducting a research survey of 385 consumers in Palladium Store supermarket located in northern Tehran. The questionnaire for this study is based on the standard questionnaires by Porrral & Mangin that analyze the independent variables (price, familiarity and subjective store image) and dependent variables (purchase intention and loyalty) and moderator variable (trust) based on structural equation modeling (SEM). The questionnaire consists of 19 items, and the Cronbach's alpha for the questionnaire is 0.879. The results of this study showed that familiarity with the brand and store image have positive and significant influence on consumer loyalty and purchase intention, and trust moderates their impact on loyalty and purchase intention. Keywords: store brand, trust, purchase intention, consumer behavior, Palladium shopping mall JEL Classifications: D1, M3